The role of smes for development: a literature review - Nelson Duarte (European Regional Science Association (ERSA), 2004)
The role played by SMEs in any society is undoubtedly important, for instance, in Portugal around 98% of the industrial fabric is composed by SMEs. Nowadays, entrepreneurship and firm creation is mostly related to small and micro firms, which lead us to look at them as an important development agent in any society. Most of times, firms are seen as a black box on what concerns to development however the measures taken by them, entrepreneurial strategies, and entrepreneurship actions, have influence in the development theatre. At the same, not only the SMEs as a group of firms (industrial sector) must be taken into consideration, but also many factors inside the firm, such as the quality of management, human resources, or innovation factors. This work intends to present the state-of-art on the subjects relating SMEs and development, trying to find out how the SMEs are related to development, which factors are taken into consideration when the role of these firms are analysed, for instance, innovation factors, human resources, or the firm revenues. It is widely accepted that SMEs are an important development agent, but sometimes they are analysed not like an agent by themselves, but as a group of firms creating (the group) another agent. This group might be a cluster, an industrial district or a filière, however it is important to look to the firm by itself. The entrepreneur might take individual actions different from those followed by the group. So the small or micro firm also has an important role for development, the main idea for this work is to find out some important initial literature on SMEs and development, trying to get a perception of the role played, not only on what concerns to enterprises creation, but also on the strategies adopted by these type of enterprises to overcome the bottleneck of regional development. Keywords: Development, SMEs, Entrepreneurship
Keywords: 330; Development; SMEs; Entrepreneurship